WHARF STRUCTURAL DESIGN FOR CONTAINER TERMINAL IN LAMONGAN, EAST JAVA - Rivanditra Purnawan - Nim: 15513013, Rafsa
Indonesia as an archipelagic country which respective islands are linked by the oceans has a great urgency to meet the connectivity needs between their islands. One of the efforts in supporting inter-island connectivity is by utilizing sea transportation mode that requires port as its transportation nodes. The infrastructure that is very important in supporting the journey of a port is a wharf. The wharf needs to be designed in such a way as to be able to remain firmly standing and survive from the brunt of the outer forces acting upon it. This Final Project contains the process of designing the deck on pile type wharf which is connected from the mainland by trestle to the planned water depth. The design of the dock structure begins by collecting environmental data including wind, tide, soil and earthquake data. The data are then processed for consideration in forecasting extreme conditions that may occur in the future so that the built wharf structure has a high probability to survive in the most extreme conditions at the site of the plan. The design of the wharf structure is done using SAP2000 software. The output of this software consists of unity check ratio, deflection, and inner forces acting on each structural elements of the wharf. The structural analysis output of the SAP2000 software is then used as data in designing the configuration of structural element reinforcement that meets the needs, and determines the depth of the pile needed to accommodate the sufficient bearing capacity of the soil.